PERSPECTIVES OF GERMANY INVESTMENT POLICY IN UKRAINE - Атаманчук, Заріна; Писаренко, Антон (SWorldJournal, 2022)
Since 2014, internal political upheavals in Kyiv, the conclusion of a major Association Agreement between Ukraine and the EU, the annexation of Crimea by Russia, the start of hostilities in the east of Ukraine and Germany's participation in further peace